2009
DOI: 10.1016/j.clinph.2009.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the degree of motor unit short-term synchronization and recurrence quantification analysis of the surface EMG in two human muscles

Abstract: The study provides a systematic evaluation of a technique previously proposed for the estimation of a clinically relevant characteristic of motor unit behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
2
12
2
Order By: Relevance
“…As compared to the coefficient of determination of 70% reported in the ECR muscles by Del Santo et al (2006), our study, yielded variations in EMG DET that were only poorly explained by variation in motor unit synchronous impulse probability and frequency across the population of motor unit pairs tested (5 and 6%, respectively). In a recent study, no correlation at all was reported to occur between EMG DET and motor unit synchronous impulse frequency in two muscles showing a marked difference in synchronization strength (Dideriksen et al, 2009). It must be noted that in our study and that of Dideriksen et al (2009), EMG DET was related to different amounts of motor unit synchrony observed in natural conditions whereas in Del Santo et al (2006Santo et al ( , 2007, motor unit synchrony was pharmacologically enhanced by increasing recurrent inhibition activity with l-acetylcarnitine injection.…”
Section: Relationship Between Motor Unit Synchrony and Emg Detcontrasting
confidence: 66%
See 4 more Smart Citations
“…As compared to the coefficient of determination of 70% reported in the ECR muscles by Del Santo et al (2006), our study, yielded variations in EMG DET that were only poorly explained by variation in motor unit synchronous impulse probability and frequency across the population of motor unit pairs tested (5 and 6%, respectively). In a recent study, no correlation at all was reported to occur between EMG DET and motor unit synchronous impulse frequency in two muscles showing a marked difference in synchronization strength (Dideriksen et al, 2009). It must be noted that in our study and that of Dideriksen et al (2009), EMG DET was related to different amounts of motor unit synchrony observed in natural conditions whereas in Del Santo et al (2006Santo et al ( , 2007, motor unit synchrony was pharmacologically enhanced by increasing recurrent inhibition activity with l-acetylcarnitine injection.…”
Section: Relationship Between Motor Unit Synchrony and Emg Detcontrasting
confidence: 66%
“…In a recent study, no correlation at all was reported to occur between EMG DET and motor unit synchronous impulse frequency in two muscles showing a marked difference in synchronization strength (Dideriksen et al, 2009). It must be noted that in our study and that of Dideriksen et al (2009), EMG DET was related to different amounts of motor unit synchrony observed in natural conditions whereas in Del Santo et al (2006Santo et al ( , 2007, motor unit synchrony was pharmacologically enhanced by increasing recurrent inhibition activity with l-acetylcarnitine injection. Another major methodological difference is that, in the two studies published by Del Santo et al (2006Santo et al ( , 2007, EMG DET values obtained across single 5-s periods were related to synchrony indices obtained across whole recordings lasting 2-3 min.…”
Section: Relationship Between Motor Unit Synchrony and Emg Detcontrasting
confidence: 66%
See 3 more Smart Citations